Syntax Struggles: A Case Study of English as Second Language Acquisition in a 6-Year-Old Child - Dzikri Ilma; Rusdi Noor Rosa; Alemina Br. Perangin-Angin (JL3T (Journal of Linguistics, Literature and Language Teaching))
This study investigates the second language acquisition of Alesha, a 6-year-old girl. Despite mastering her mother tongue, Indonesian, Alesha has been exposed to English since a young age through interactions with her parents and media. The study focuses on Alesha's ability of her second language in daily contexts, particularly in interactions with her mother. Employing a qualitative descriptive approach, the research aims to comprehend phenomena by providing detailed descriptions and interpreting their meanings, without using numbers or statistics. Data collection involves interviews, where conversations between the mother and child are recorded, with the researcher noting relevant information. Findings reveal that although Alesha can communicate in English, there are syntactic constraints evident in her sentence patterns, particularly regarding the use of auxiliary verbs and distinguishing between plural and singular nouns. These findings align with observations that Alesha's exposure to her second language is inconsistent. The article highlights the importance of consistency in second language learning patterns for children, whether through parental involvement or media exposure. Research on Alesha is beneficial for parents, language educators, and researchers in understanding children's language development and designing more effective teaching stategies. Furthermore, those interested in researching the same topic are advised to conduct a research with subjects of the same age as Alesha, as well as analysis with other related variables, for a better understanding of second language acquisition in 6-year-old children.